1985
DOI: 10.1136/adc.60.5.420
|View full text |Cite
|
Sign up to set email alerts
|

Long term prognosis of recurrent haematuria.

Abstract: A long term follow up study of 100 children referred with recurrent haematuria for at least one year to two regional paediatric nephrology units is described. The mean duration of follow up was 8-2 years. An adequate renal biopsy was obtained in 96 and eight cases of Alport's syndrome and 10 of IgA nephropathy were diagnosed (20% and 26% respectively of the biopsies examined by electron microscopy and immunofluorescence). Five patients developed end stage renal failure and six hypertension requiring treatment,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

1989
1989
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Hematuria co-existing with proteinuria correlated well with the severity of the morphological glomeruli alterations in symptomless proteinuria and hematuria of the school-age population [14,15]. Hisano et al reported that a renal biopsy on patients with urine abnormalities detected by urine screening revealed IgAN in 53.7% of the patients testing positive for both proteinuria and hematuria [16].…”
Section: Discussionmentioning
confidence: 97%
“…Hematuria co-existing with proteinuria correlated well with the severity of the morphological glomeruli alterations in symptomless proteinuria and hematuria of the school-age population [14,15]. Hisano et al reported that a renal biopsy on patients with urine abnormalities detected by urine screening revealed IgAN in 53.7% of the patients testing positive for both proteinuria and hematuria [16].…”
Section: Discussionmentioning
confidence: 97%
“…Hematuria coexisting with proteinuria was well correlated with the severity of morphological changes of glomerular structure of kidneys in the pediatric patients with asymptomatic proteinuria and hematuria. 27,28…”
Section: Discussionmentioning
confidence: 99%
“…Most consider the finding to be non-specific. However, reports of large series of biopsies performed for hematuria [7][8][9][10] fail to note this positive IF finding, which would have been expected to occur randomly if it were a non-specific finding. Vascular C3 deposits have been considered to be non-specific as they have been seen in conjunction with IgA nephropathy [11,12] and hypertension-related renal disease [13,14].…”
Section: Discussionmentioning
confidence: 93%